Dynamic information routing in complex networks - Christoph Kirst (Nature Portfolio, 2016)
Flexible information routing underlies the function of many biological and artificial networks. Here, the authors present a theoretical framework that shows how information can be flexibly routed across networks using collective reference dynamics and how local changes may induce remote rerouting.